Optimalisasi Tanah Kas Padukuhan melalui Budidaya Cabai dan Pengembangan Tanaman Apotik Hidup sebagai Upaya Pemberdayaan Masyarakat Padukuhan Pudak - Joko Riyanto; Cindy Sekarwati Amalia; Anindya Citra Maharani Ariyadewi; Hana Hanindita; Alvrisa Ayumi Russari; Amanah Farahdhita; Vuvut Permata Sari PH; Anjayna Rindi Prangesti; Ni Putu Eka Saraswati; Mentari Nurlita Ramadhan (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
This community service activity aims to maximize the use of village land thru chili cultivation and the development of medicinal plants as a means of community empowerment. The activity was carried out in Padukuhan Pudak, Kalurahan Jepitu, Kapanewon Girisubo, Gunungkidul Regency as part of the implementation of the Community Service Program (KKN). The method of implementing the activities includes the stages of observation and identification of land potential, coordination with the village government and the community, land preparation, planting, socialization to the community, and monitoring the development of the plants. The village's communal land, which had previously not been well-utilized, was then processed and used for two types of cultivation: chili pepper cultivation and the cultivation of medicinal plants, which include ginger, turmeric, galangal, and lemongrass. The results of the activities show that the utilization of the land has been able to increase community awareness in effectively using local resources and enhance the community's knowledge of basic plant cultivation techniques. In addition to potentially providing economic benefits thru chili harvests, the presence of medicinal plants can also support community independence in using family medicinal plants. Thus, this activity not only enhances the utilization of village land but also promotes community empowerment thru increased knowledge, participation, and sustainable management of local resources.